M. A. Ayuh. Made in Jamaica: The Development of Manufacturing Sector. Baltimore: The Johns Hopkins University Press. 1981. xxii+128 pp. (The Pakistan Development Review, 1986)
Jamaica, known in the world for her rich deposits of bauxite ore, is a small Caribbean country with an area of 10991 square kilometers and a population of just over two million individuals. This beautifu11and, which was described by Columbus as "The fairest isle that eyes have beheld" has developed a remarkably diversified manufacturing sector starting from a modest industrial base. Jamaica's manufacturing industry enjoyed a respectable growth rate of about 6 percent per annum during the good old days of the euphoric '50s and '60s. However, those bright sunny days ''when to live was bliss" were followed by the chilling winter of much subdued progress. The rise and fall of growth have aroused considerable interest among economists and policy• makers. The book under review probes the causes of this behaviour by analysing key characteristics of Jamaican manufacturing sector and tracing its path of evolution.